ChemInform Abstract: A General Method for the Direct Transformation of Common Tertiary Amides into Ketones and Amines by Addition of Grignard Reagents. Issue 39 (September 2015) - Huang, Pei‐Qiang; Wang, Yu; Xiao, Kai‐Jiong; Huang, Ying‐Hong
Abstract The title reaction is promoted by Tf2O and can be viewed as the acrylation of Grignard reagents using amides as stable and selective acylation agents.